Performance Analysis of Centrifugal Pumps Before and After Wear Ring Restoration - Moh Sahal Rifai; Nanang Ruhyat; Arief Surachman (Universitas Mercu Buana, 2025)
A pump is a mechanical device used to move fluids from a lower elevation to a higher one. In general, pumps are classified into two types: positive displacement pumps and non-positive displacement pumps. Centrifugal pumps fall into the latter category and operate by converting mechanical energy into kinetic energy to transport fluids. A centrifugal pump consists of several key components, including the casing, shaft, bearing, coupling, and impeller. In the case of closed impeller-type centrifugal pumps, wear rings (wearing components) are installed to provide a clearance between the impeller and the casing, preventing physical contact during operation. The size of this clearance significantly affects pump performance. Wear ring damage can result from mechanical wear, corrosion, cavitation, and fatigue, leading to performance losses such as reduced flow rate, lower pressure, and decreased efficiency. This research aims to analyze the effect of wear ring damage on the performance of a centrifugal pump by comparing operational data before and after repair of the wearing components. The performance parameters evaluated include pump head, pressure, hydraulic power, motor power, and overall efficiency. Data were collected through a structured procedure consisting of preparation, testing, measurement, and analysis. Prior to repair, the pump operated with a wear ring clearance of 1.2 mm, resulting in an average efficiency of 8.5% and a flow rate of 0.000646 m³/s. After the clearance was restored to 0.43 mm, the average efficiency increased to 15.5%, with a corresponding flow rate of 0.000932 m³/s. These results demonstrate that maintaining wear ring clearance within recommended standards significantly improves pump performance, highlighting the importance of regular maintenance and timely component repair.